Re-distribution of residual stress in polymer extrusion: An eccentric approach - Suleyman Deveci (Elsevier, 2021)
The development of residual stresses in plastic pipes due to post-die cooling rate differences of the polymer melt was investigated using concentric and eccentric circular geometries in the shape of an annular tube. Heat transfer simulations were performed to understand the effect of non-uniform wall thickness on the temperature and residual stress profiles of melt solidified polymers. Residual stress measurements and thermal analysis of the end products and heat transfer simulation of the post die cooling process were evaluated to understand the change in stress state in the polymer products as a function of temperature. This was done through an example of extruded high-density polyethylene pipes using an industrial scale extrusion line. The outcome of this research helps better understanding of the melt solidification process and its effect on application related properties in a way that was never presented before.